Post Traumatic Stress Disorder and Adaptive Capacity in Victims of Intimate Partner Violence (2012)
The goal of this article was to identify the existing relationship between Post Traumatic Stress Disorder (PTSD) and the adaptive capacity in a group of victims of intimate partner violence residing in Medellin (Colombia). The sample consisted of 26 people, both male and female selected from different health and social centers. The instruments used were the PTSD Symptom Severity Scale and the Maladjustment Scale. Descriptive statistics and Pearson’s Correlation Coefficient were used for data analysis. The results reinforce the initiative of considering PTSD as a diagnostic category unmistakably associated to intimate partner violence; 84.2% of the sample reported Post Traumatic Stress Disorder symptomatology, mainly avoidance and hyperarousal, as well as somatic manifestations. Maladjustment levels were highly elevated, 93.2% average, the areas with the lowest level of adaptive capacity were marital life and family life, while maladjustment levels exhibited significant associations with overall PTSD and hyperarousal (p